Evaluation of the Plant Theory - Scholten, Jan (Homœopathic Links, 2017)
This article discusses the value of the Plant theory in practice. This was done by informally asking around 10 homeopaths about their experience with the Plant theory. The complexity of the Plant kingdom makes several factors to be ascertained. This complexity takes time to learn. Though the benefits are great once it is learned. The learning is more than worth the time it takes. It opens the whole botanical world.
Keywords: Plant theory; Plant kingdom; Analysis; Botany